Digitizing parking area availability information using Canny algorithm based on Android application: Digitalisasi informasi ketersediaan lahan parkir menggunakan algoritma Canny berbasis aplikasi Android - Suci Ramadona; Wira Indani; Mochamad Susantok; Maya Rahayu (Jurusan Teknik Elektro, Politeknik Negeri Bandung, 2022)
The Covid-19 pandemic is a factor in accelerating digital transformation in all aspects of community needs, especially in the parking area. Unmonitored and non-digitalized parking lots can cause delays that increase the transmission of Covid-19. In this study, a parking digitization system is created to make it easier for the public to know how dense is the area of ??the location to be visited, as well as a vacant area that can be occupied to park vehicles by users of the parking lot through a smartphone application. This study uses the Canny algorithm through an optical flow process captured by the IP Camera, next the data is processed and presented in the Android application. From the system that has been made, the system detects the presence of vehicles with an accuracy of above 95%.